BOREAL UPPER BATHONIAN IN THE VOLGA RIVER MIDDLE COURSES (AMMONITES AND STRATIGRAPHY) - Gulyaev D.B.; Kiselev D.N. (My University, 1999)
Deposits and boreal marine fossils of the Upper Bathonian are discovered in the Volga River middle courses, the central Russian plain. The deposits occur below the elatmae Zone considered as the East European equivalent of the standard herveyi Zone, the basal one in the West European Callovian. In generic and specific composition, the discovered ammonite assemblage is similar to those of the Upper Bathonian from eastern Greenland and Spitsbergen. Five ammonite species are described. One of them, Cadoceras (Catacadoceras) infimum, is new, whereas Kepplerites (Kepplerites) svalbardensis Sok. et Bodyl., K, (K.) cf. rosenkrantzi Spath, and K. (Toricellites) pauper Spath have been known before in the Arctic regions only. The local biostratigraphic infimum Zone, which immediately underlies the elatmae Zone, can be correlated with a basal part of the calyx Zone in eastern Greenland and with the upper part of the barnstoni Zone in northern Siberia. Its stratigraphic position in the West European standard is nor very clear and supposed to be in the interval spanning the upper part of the orbis Zone and the entire discus Zone. The data obtained suggest that the Boreal sea transgression advanced in the Russian platform to the Volga River middle courses at the end of the Bathonian.
Keywords: Bathonian; Mesozoic::Jurassic::Middle::Bathonian; Мезозой::Юрская::Средний::Батский